Can virtual reality be used to investigate persecutory ideation? - Freeman, D; Slater, M; Bebbington, P; Garety, P; Kuipers, E; Fowler, D; Met, A; Read, C; Jordan, J; Vinayagamoorthy, V (2003)
The use of virtual reality permits individuals' reactions to standard controlled environments to be studied. It may therefore provide a means for understanding the interpretations of experience relevant to clinical disorders. The use of this technology for understanding persecutory ideation has not been investigated. A pilot study was undertaken to examine whether individuals have persecutory thoughts about virtual reality characters under controlled conditions and if there are factors that predict the occurrence of such thoughts.Twenty-four nonclinical participants entered a neutral virtual environment that contained computer-generated people. The participants completed dimensional assessments of items related to psychiatric symptoms and their thoughts about the virtual characters. Positive views about the virtual characters were common. However, a number of participants had ideas of reference and ideas of persecution about the virtual characters. Individuals who had persecutory thoughts about the virtual characters had significantly higher levels of interpersonal sensitivity and anxiety. The study provides direct evidence that individuals attribute mental states to virtual reality characters. Important for the study of clinical phenomena, some individuals have thoughts of a persecutory nature about virtual characters. Additionally, the findings indicate that feelings of interpersonal vulnerability and anxiety may directly contribute to the development of persecutory ideation in response to essentially neutral contexts. Virtual reality may prove to be a valuable methodology for developing an understanding of persecutory ideation.